Strength and stiffness characteristics of self-drilling screw lap-joints - Marimuthu, V.; Palani, G.S.; Kumar, S. (Journal of Structural Engineering, 2024)
Self-drilling screws (SDS) are generally used to connect secondary structural elements such as purlin, roofing sheets, wall and side claddings etc, in which the screw head is in contact with thin sheets. Attempts have been made to use these fasteners to connect primary structural members made up of cold-formed steel (CFS) sections, where it is expected that screw heads will be in contact with thick sheets, for which guidelines are not available. The existing guidelines addresses the configuration, where the screw head is in contact with thin sheets. As these fasteners are used to connect primary load carrying members, the performance of SDS joints (SDSJ) play a major role in analysis and design of such structures. In view of this, experimental studies have been conducted on SDS lap-joints (SDSLJ) under tensile shear loading with different combinations of plate thicknesses and number of screws. The performance of the SDSLJ has been studied in terms of load-displacement behavior and failure modes. The specimens failed by bearing and tilting, shearing of screws and net-section fracture. The obtained failure mode and strength of specimens are used to validate the existing guidelines and to evaluate the stiffness of SDSJ. It is found that the existing guidelines predict the failure mode and strength closer to that of the experiment. This paper presents the details of the experiments, methodology for evaluation of strength and stiffness of SDSJ and the comparative studies.